Gallic Acid: Review of the Methods of Determination and Quantification - Alencar Fernandes, Felipe Hugo [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2016)
Gallic acid (3,4,5 trihydroxybenzoic acid) is a secondary metabolite present in most plants. This metabolite is known to exhibit a range of bioactivities including antioxidant, antimicrobial, anti-inflammatory, and anticancer. There are various methods to analyze gallic acid including spectrometry, chromatography, and capillary electrophoresis, among others. They have been developed to identify and quantify this active ingredient in most biological matrices. The aim of this article is to review the available information on analytical methods for gallic acid, as well as presenting the advantages and limitations of each technique.
Keywords: Analytical methods; gallic acid; polyphenol